On the other end of the line: Extracellular vesicle-mediated communication in glaucoma - Lucci, Cristiano; De Groef, Lies (Frontiers in Neuroanatomy, 2023)
In the last decade, extracellular vesicles (EVs) have emerged as a promising field of research due to their ability to participate in cell-to-cell communication via the transfer of their very diverse and complex cargo. The latter reflects the nature and physiological state of the cell of origin and, as such, EVs may not only play a pivotal role in the cellular events that culminate into disease, but also hold great potential as drug delivery vehicles and biomarkers. Yet, their role in glaucoma, the leading cause of irreversible blindness worldwide, has not been fully studied. Here, we provide an overview of the different EV subtypes along with their biogenesis and content. We elaborate on how EVs released by different cell types can exert a specific function in the context of glaucoma. Finally, we discuss how these EVs provide opportunities to be used as biomarkers for diagnosis and monitoring of disease.